Pemahaman Guru tentang Konsep Dasar Hubungan Sekolah dan Masyarakat dalam Prespektif Outcome - Indri Eka Lestari; Habibah Habibah; Anna Shofiatun Nisa; Seftiana Anindya Narfa; Nurriyanti Nurriyanti; Salma Safitri; Suhaimi Suhaimi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines teachers’ understanding of the basic concept of school community relations from an outcome prespective in elementary schools. The relationship between schools and the community plays an important role in supporting the effectiveness of educational programs and improving the quality of learning outcomes. Theacers act as key actors who connect schools with parents and the surronding community. Therefore, understanding the concept of school and community relations is essential to build effective communication and collaboration. The researgh used a qualitative approach with a literature study method. Data were collected from relevant academic sources such as journal articels, book, and previous reaseacrh related to school and community relations and educcational management. He collected data were analyzed using descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The results of the study indicate the techers’ understanding of the concept of school and community relations countributes significantly to strengthening cooperation between schools and the community. Effective collaboration can increase community partisipation, support school programs, and create positive educational outcomes for students and institutions. Thus, strengthening teachers’ understanding of school and community relations is important to improve the quality and effectiveness of education in elementary schools.